Accounts of home isolation during the COVID-19 pandemic: Case of Peruvian indigenous students - Fergusson, Lee (2022)
Most of the literature that has emerged about the impacts of home isolation during the COVID-19 pandemic suggests it causes mildly to acutely adverse psychosocial and physiological responses, particularly in children. Such responses relate to the separation children experience from their normal routine, including loneliness, anxiety, and depression, and adversities associated with school performance. In this case study, we explore the intersection between three phenomena in Perú: (1) practice of Transcendental Meditation by school students at a (2) provincial school during (3) home isolation. The study conducted semi-structured interviews at a school in Puno with seven students, three parents, and two teachers. A proto-theoretical model of stress, the stress response, and outcomes in three psychosocial categories—cognitive, affective, and conative—guide the research. Findings suggest the practice had a salutary effect on student experience and academic achievement, including multifactorial benefits related to learning, calmness, anxiety, and grades.